Recepti in napotki za krizne čase - Godina-Golija, Maja (Etnolog. Nova vrsta (Ljubljana), 2012)
The article addresses different food practices and food substitutes, in particular from the First World War. Food shortages and related famines occurred during the two world wars and partly also during the economic crisis of the early 1930s. The articles presents the publication of the first Slovenecookbook, issued during the First World War, and recipes for preparing ordinary and special dishes in times of crisis or war.
Keywords: ethnology; Etnologija; food; nutrition; Prehrana; Svetovna vojna 1914-1918; Slovenia; Slovenija; lakota; recepti; prva svetovna vojna; World War I; 1914/1918